Cyclical and linear progress in history: a comparative analysis of Ibn Khaldun, Hegel, and Toynbee - Jalal Nori, Abdulwahed; Tahir, Zhilwan (Green Five Solution, 2024)
This article explores the central historiographical debate between cyclical and linear perspectives of historical progress, focusing on the contributions of Ibn Khaldun, Hegel, and Toynbee. Ibn Khaldun's cyclical theory emphasises the rise and fall of civilisations driven by social cohesion (Asabiyyah), economic factors, and moral dynamics. Hegel, in contrast, presents a linear, teleological progression of history guided by the realisation of freedom and rationality through dialectical processes. Toynbee offers a hybrid model, blending cyclical challenges with potential linear advancements, emphasising creative responses to crises. The comparative framework examines their views on the nature of progress, the driving forces of change, and the patterns of rise and decline in civilisations. Ibn Khaldun’s focus on internal cohesion and leadership is juxtaposed with Hegel’s deterministic progression and Toynbee’s adaptive flexibility. Integrating insights from modern thinkers, this study highlights how these perspectives inform contemporary issues like nationalism, globalisation, and governance. By analysing these paradigms, the article demonstrates the enduring relevance of cyclical and linear approaches in understanding historical evolution and societal transformation.